Non-point source-driven carbon and nutrient loading to Ganga River (India). Issue 4 (21st April 2019) - Singh, Rachna; Pandey, Jitendra
ABSTRACT: This study was designed to test whether the atmospheric deposition (AD) significantly influences gross primary productivity (GPP) and dissolved organic carbon (DOC) build-up in the Ganga River. We collected data for three consecutive years (2012–2014) along with 37 km river stretch with respect to AD-input of carbon, nutrients, and surface runoff chemistry to relate changes in the river water. We found strong linkages among carbon and nutrients in AD, surface runoff and in the river. The concentration of DOC in the river was highest in the rainy season while those of dissolved inorganic nitrogen and dissolved reactive phosphorus were highest in winter. Spatio-temporal changes in DOC indicated dependence on point- and non-point sources and within-system DOC build-up. The GPP in the river increased consistently over time and significantly correlated with AD-N ( R 2 = 0.96, p < .001) and AD-P ( R 2 = 0.97, p < .001). Basin level extrapolation showed that the Ganga River Basin receives 1.81 Tg organic-C, 2.77 Tg reactive-N, and 130 Gg reactive-P annually through atmospheric deposition. Non-point source contributions of carbon and nutrients to the river were substantially higher than those of point sources. The study has relevance for regional scale carbon and nutrient budgeting and action plans for integrated river basin management.